Mental disorders in endocrinopathies - N. A. Kosenko; B. D. Tsygankov; V. G. Kosenko; M. I. Ageev; G. T. Krasil'nikov; E. F. Chebagina (Кубанский научный медицинский вестник)
This article presents a literature review of today's challenging clinical problem of mental disorders in endocrinopathy. After an introduction to the topic describes a brief history of the development of psychoendocrinology and putative mechanisms of the pathogenesis of mental disorders caused by endocrine dysfunction. Outlines the main clinical forms of mental disorders, as well as analyzes the patterns of their clinical dynamics. Marked clinical manifestations caused by a non-specific impact of endocrine dysfunction, as well as the specific features of each individual endocrinopathy. In conclusion, describes an integrated approach for the treatment and rehabilitation of patients with these forms of pathology. Given the prevalence of endocrinopathies and frequent combinations thereof with mental disorders information on this issue is needed for professional doctors of all specialties.